Neuropsychiatric Morbidity And Quality Of Life Among A Geriatric Population Attending A Nigerian Teaching Hospital - Kareem, Yesiru Adeyemi; Adesina, Ismail Olaiitan; Ali, Fatima Abba; Adigun, Agboola Jamiu; Davuruk , Dennis Amos; Ogualili , Placidus Nwakuba (Indonesian Scientific Publication, 2024)
The World Health Organization (WHO) reports the global impact of chronic conditions as profound, associated with neuropsychiatric comorbidities, and thus affecting Quality of Life (QoL). This study assessed neuropsychiatric morbidity and the association with QoL among older adults with chronic conditions at the University of Maiduguri Teaching Hospital, Nigeria. A comparative cross-sectional analytic design was utilised to recruit 327 older adults aged 60 years and above for six months, then proportionally distributed into four groups. The Community Screening Instrument for Dementia (CSID), Geriatric Depression Scale (GDS-30) and WHO Quality-of-Life for the Old (WHOQOL-OLD) were administered. Data was analysed using the SPSS version 27.0. Neuropsychiatric morbidity was associated with lower QoL in all four groups. In HTN, QoL was significantly lower in one domain, AUT (t=3.95, p<0.001). For DM only, in two, AUT (t=4.35, p<0.001) and DAD (t=6.65, p<0.001). For Arthritis only, in three, SAB (t=6.92, p<0.001), AUT (t=11.46, p<0.001), and PPF (t=4.02, p<0.001). In HTN+DM, in two, SAB (t=5.37, p<0.001) and AUT (t=2.51, p=0.02). This study reported a low QoL in the presence of neuropsychiatric morbidity. The implication of this is the need to be proactive in screening older adults with these physical health conditions for neuropsychiatric morbidity. Their early detection will facilitate timely intervention, which in turn improves the QoL of older adults with chronic medical conditions.